Mild drought in the vegetative stage induces phenotypic, gene expression, and DNA methylation plasticity in Arabidopsis but no transgenerational effects. (13th March 2020) - Van Dooren, Tom J M; Silveira, Amanda Bortolini; Gilbault, Elodie; Jiménez-Gómez, José M; Martin, Antoine; Bach, Liên; Tisné, Sébastien; Quadrana, Leandro; Loudet, Olivier; Colot, Vincent
Abstract : A comprehensive phenotypic analysis in five Arabidopsis accessions combined with methylome and transcriptome analyses in the Col-0 reference accession indicate plasticity to mild drought but no transgenerational effects or inherited stress memory. Abstract: There is renewed interest in whether environmentally induced changes in phenotypes can be heritable. In plants, heritable trait variation can occur without DNA sequence mutations through epigenetic mechanisms involving DNA methylation. However, it remains unknown whether this alternative system of inheritance responds to environmental changes and if it can provide a rapid way for plants to generate adaptive heritable phenotypic variation. To assess potential transgenerational effects induced by the environment, we subjected four natural accessions of Arabidopsis thaliana together with the reference accession Col-0 to mild drought in a multi-generational experiment. As expected, plastic responses to drought were observed in each accession, as well as a number of intergenerational effects of the parental environments. However, after an intervening generation without stress, except for a very few trait-based parental effects, descendants of stressed and non-stressed plants were phenotypically indistinguishable irrespective of whether they were grown in control conditions or under water deficit. In addition, genome-wide analysis of DNA methylation and gene expression in Col-0 demonstrated that, while mild drought induced changes in the DNA methylome of exposed plants, these variants were not inherited. We conclude that mild drought stress does not induce transgenerational epigenetic effects.